Synthesis of Majusculamides A and B - Nakajima, Daisuke; Sueyoshi, Kosuke; Orihara, Kensuke; Teruya, Toshiaki; Yokoshima, Satoshi (Synlett, 2019)
The synthesis of two marine lipodipeptides, majusculamides A and B, is described. The key feature of this synthesis is the stereoselective construction of an α-methyl-β-keto-carboxamide moiety.
Keywords: marine natural products; peptides; polyketides; β-ketoamide; asymmetric aldol reaction